The transformation of science-learning: the role of scientific inquiry and interactive technology in elementary schools - Yunita Sari; Jupriyanto Jupriyanto; Rida Fironika Kusumadewi (Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking skills have an important role in learning science in elementary school. But in reality, science learning in grade V of elementary school has not been optimally directed to develop students' critical thinking skills. The limitations of interesting learning media that are in accordance with the characteristics of elementary children are one of the causes of students' low interest and motivation to learn science subjects The objectives of the research are (1) Producing interactive multimedia with  a scientific inquiry approach, (2) Obtaining interactive multimedia  feasibility data with a scientific inquiry approach and (3) Obtaining effectiveness test datacritical thinking skills in improving  critical thinking skills of elementary school students. This development research uses the ADDIE model, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation  with mixed method research methodology.  The results of the research from expert validation in both aspects of material, media, language, and learning show that interactive multimedia with  a scientific inquiry approach is valid for use. The response of teachers and students to interactive multimedia with  a scientific inquiry approach is in the category of very good. The effectiveness test by implementing the scientific inquiry approach showed that interactive multimedia science was effective and practical in improving the critical thinking skills of Grade V elementary school students. It can be concluded that interactive multimedia with  a scientific inquiry approach can be used as a learning medium to stimulate students to reason and think critically in improving the quality of science learning.